2000
DOI: 10.2527/2000.7861467x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between reaction to sudden, intermittent movements and sounds and temperament.

Abstract: Casual observations indicated that some cattle are more sensitive to sudden movement or intermittent sound than other cattle. Six commercial livestock auctions in two states and a total of 1,636 cattle were observed to assess the relationship between breed, gender, and temperament score on the response to sudden, intermittent visual and sound stimuli, such as the ringman swinging his arm for a bid and the sound of him briefly yelling a bid. A 4-point temperament score was used to score each animal while it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 28 publications
1
45
0
8
Order By: Relevance
“…EPAS1 is involved in angiogenesis and Bionaz et al Mutations in CDH23 are associated with hearing loss in humans, including through the condition called Usher syndrome (Wagatsuma et al 2007). While this relationship may not seem relevant to dairy production, Lanier et al (2000) reported a significant difference in sensitivity to sound between Holstein dairy cattle and beef cattle. Moreover, CDH23 is believed to exert its effect through the formation of a transmembrane complex with the PDZ domains of the protein harmonin (Siemens et al 2002).…”
Section: Resultsmentioning
confidence: 93%
“…EPAS1 is involved in angiogenesis and Bionaz et al Mutations in CDH23 are associated with hearing loss in humans, including through the condition called Usher syndrome (Wagatsuma et al 2007). While this relationship may not seem relevant to dairy production, Lanier et al (2000) reported a significant difference in sensitivity to sound between Holstein dairy cattle and beef cattle. Moreover, CDH23 is believed to exert its effect through the formation of a transmembrane complex with the PDZ domains of the protein harmonin (Siemens et al 2002).…”
Section: Resultsmentioning
confidence: 93%
“…On average, young cattle were observed to be more temperamental than older cattle (Voisinet et al, 1997;Lanier et al, 2000) and with ageing, cattle behaviour was found to be more consistent over time (Gibbons et al, 2011;Haskell et al, 2012). These modulations of behaviour through individual experiences and therefore through ageing are assumed to evolve from changes in the reactivity of the nervous system (Grandin and Dessing, 1998).…”
Section: Cattle Temperament and Production Systemsmentioning
confidence: 99%
“…In general, Bos indicus breeds were found to be more excitable than Bos taurus breeds (Voisinet et al, 1997). Dairy cattle showed a higher approachability than beef cattle (Murphey et al, 1980) and were more reactive to sudden noises during cattle auctions (Lanier et al, 2000). Moreover, numerous behaviour studies were conducted for different beef breeds enabling a temperament ranking from more calm breeds like Herford and Angus to breeds that are more temperamental like German Simmental or Charolais (Morris et al, 1994;Gauly et al, 2002;Hoppe et al, 2010).…”
Section: Genetic Background Of Cattle Temperamentmentioning
confidence: 99%
“…It is well documented that noise is a stress factor in farm animals (Forsling et al 1984;Stephens et al 1985;Agnes et al 1990;Talling et al 1996;Waynert et al 1999;Lanier et al 2000;Schaffer et al 2001;Otten et al 2004;Kanitz et al 2005;De la Fuente et al 2007). Grandin (1996) and Geverink et al (1998) pointed out the instances of poor welfare in slaughterhouses due to excessive noise.…”
mentioning
confidence: 99%